Indolent T-Cell Lymphoproliferative Disease: A Rare Case of a Benign Lymphoma of the Gastrointestinal Tract With Extra-Gastrointestinal Involvement. Issue 10 (12th October 2022) - David, Robin; Mishra, Kajali; Gilbert, Emily R.; Mirza, Kamran M.; Hendler, Steven
ABSTRACT: Indolent T-cell lymphoproliferative disease of the gastrointestinal (GI) tract is an exceedingly rare benign proliferation of clonal and mature-appearing lymphoid cells originating from the GI tract. We discuss the case of a 52-year-old woman with indolent T-cell lymphoproliferative disease of the GI tract manifesting as chronic diarrhea and profound weight loss. Interestingly, the patient also had extra-GI involvement of her disease process, which has not been previously reported. Our patient was managed with steroids with improvement in symptoms and weight gain. We provide a review of the literature to highlight the importance of early recognition and intervention of this disease entity.